Hilltop Incorporated - Baldevia, Joanne; Bayona, Genevieve; Darroca, Rannen; Gumban, Gynnyn; Managuit, Catherine
Executive Summary-(The Proponents)-The Dairy Factory shall be registered as a partnership with a name Hilltop Company to be owned by five partners, Rannen Darroca, Genevieve Bayona, Gynnyn Gumban, Catherine Managuit, and Joanne Baldevia. The partners decided to invest in Barotac Nuevo because the business environment is favorable. There are huge demand for milk in the area but the supply is inaccessible and oftentimes not affordable to the common people. Because of these, the five partners decided to invest in the Dairy Factory business. The said five partners are graduate of business courses, since all of them have background in business management, it will not be a problem to manage such kind of business. With regards to the financing needs, the five partner have some money of their own or they could borrow in their respective names to invest in the Hilltop Company. The contribution of the five partners would be sufficient to augment the limited requirements of the operating business. The business will be a limited partnership because there will only be two general partners who will render their service. They are Rannen Darroca and Catherine Managuit who will act as general manager and finance officer respectively. They will also be called managing partners. Since, these partner will also contribute cash, they will be likewise called limited partners. On the other hand, the three remaining partners will be considered limited partners because they will contribute their money to the partnership. (Description of the Project)-The importance of producing milk in the Philippines need not be over emphasized. Every year the country's dairy needs are filled by the milk reprocessing and repackaging sectors which import milk from countries such as Australia, New Zealand and the Netherlands. These could be gleaned from the reported importation value in the last decade of over 1.5 B dollar for 12 tons of milk in liquid milk equivalent. Increases in both quality and value of milk and milk products importation is expected to accelerate as the population sustains its growth. Unless local production responds to its own compensating increase, dairy import is expected to shoot-up. Moreover, the widening gap of the supply-demand for this essential food commodity will exacerbate the malnutrition problem especially among growing children and infants. These has been the considerations which attracted the proponents to engage in such kind of business. The advent of APEC is a scenario that underscores the need to intensify efforts toward developing local dairy industry. However, as a University of the Philippines graduate with social responsibility imbued in one's mind as Iskolar ng Bayan, and knowing that the Philippines is still an agricultural-based economy, we want to contribute to the attainment of goals to increase farm incomes, make efficient utilization of farm resources, provide rural employment opportunities and general improvement in the quality of life of the people. (Summary of conclusions and findings) a) Market Aspect-The market study revealed that there are enough supply of cows, land, machineries and equipment, furnitures and fixtures, raw materials for the existence of the Dairy Factory in Barotac Nuevo, Iloilo. It also showed that there is a very big gap between the supply and demand condition of milk in the Province of Iloilo particularly in the fourth district. Hence, there is a ready market for this business in the Province of Iloilo. b) Technical study-The technical study showed that the product to be offered are needed by the people especially children and infants. The technical facilities which are needed to start the operation of the business are readily available. Moreover, the labor and other technical skills needed are also relatively available for existence. c)Management aspect-The business organization appropriate for the company is a limited partnership because it can be formed on a short period of time and capitalization can be raised easily. A line authority among the personnel and a flat organizational structure is suitable for the company so that there will be delineation of authority and responsibility. The positions to be filled are available and relatively easy to fill-up and do not require much training, expensive and academic qualifications. The salaries to be paid to the personnel are reasonable and appropriate to the responsibilities handled by each of them. Finally, the organization of the business is feasible because of the availability of the personnel and the simplicity of the internal structure of the company. d)Financial aspect-The project requires large investment but minimal returns. The average return to the investment for five years is almost 22.64% which is only favorable if the investment in other business entity is less than 22.64%. The business' results of operations and financial conditions will be favorable. e)Social Desirability-The project will help in the improvement of the nutritional status of the people considering that they are given easy access to outlet of milk at an affordable price. It will also help generate full time jobs. All things being equal, priority should be given to the applicants residing near the project area. The project would have no adverse effect on the environmental condition in the project area.The manure is known to have fertilizer ideal for maintaining the fertility of the soil and improving its physical structure. To minimize pollution through water, necessary provisions are made in the design of the plant and its operation. A provision for treating the affluent water was meticulously considered. f)Project Timetable-If the investors will pursue the implementation of this project feasibility study, it will start on June 1997. Preparation of production site and construction of the building and landscaping will start on October 1997 to February 1998 after the investment by partner and the organization of the partnership. Acquisition of the assets will be made after the construction of the building and landscaping together with hiring of personnel. Breeding cows which are 6 months pregnant will be purchased on February 1998. Project timetable is shown on Table 1.